Differentiating Dynamic Cerebral Autoregulation Across Vascular Territories - Reehal, Navpreet; Cummings, Stephanie; Mullen, Michael T.; Baker, Wesley B.; Kung, David; Tackett, William; Favilla, Christopher G. (Frontiers in Neurology, 2021)
Objective: Transcranial Doppler is commonly used to calculate cerebral autoregulation, but measurements are typically restricted to a single cerebral artery. In exploring topographic heterogeneity, this study reports the first thorough comparison of autoregulation in all major cerebral vessels. Methods: In forty healthy adults, flow velocity was monitored in the anterior, middle, and posterior cerebral arteries, and synchronized with arterial blood pressure. A transfer function analysis provided characteristics of autoregulation by quantifying the relationship between blood pressure and cerebral blood flow velocity. Results: Phase, which quantifies the time course of autoregulation, was similar in all vessels. Gain, which quantifies the magnitude of hemodynamic regulation, was lower in posterior cerebral artery, indicative of tighter regulation. However, after adjusting for baseline flow differences in each vascular territory, normalized gain was similar in all vessels. Conclusions: Discriminating dynamic cerebral autoregulation between cerebrovascular territories is feasible with a transcranial doppler based approach. In the posterior cerebral artery of healthy volunteers, absolute flow is more tightly regulated, but relative flow regulation is consistent across cerebrovascular territories. Significance: The methodology can be applied to focal disease states such as stroke or posterior reversible encephalopathy syndrome, in which the topographic distribution of autoregulation may be particularly critical.